A fuzzy comprehensive evaluation model for smart city application. (30th April 2020) - Liu, Huaihui; Zhang, Zhiqing; Sun, Zhijie
The relationship between the police and citizens directly reflects that between the authority and the public, which play an important role in the social stability. Firstly, we design a hierarchy evaluation index system model about the harmony degree, with the help of questionnaires, based on the principle of designing an evaluation index system and five major factors that impact the police-citizen harmony relationship. Secondly, we set up a fuzzy comprehensive evaluation model based on an improved analysis hierarchy process (AHP). And then we make an empirical research on the harmony degree with the help of the model we set up. Finally, based on the conclusion of the empirical research, we make a propose to the government and the security department about how to promote the construction of the harmony police-citizen relationship. The research enriches the methods and means of evaluation on the harmony degree and exemplifies the empirical research.